The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1177/14777509221104703
|View full text |Cite
|
Sign up to set email alerts
|

Non-therapeutic penile circumcision of minors: current controversies in UK law and medical ethics

Abstract: The current legal status and medical ethics of routine or religious penile circumcision of minors is a matter of ongoing controversy in many countries. We focus on the United Kingdom as an illustrative example, giving a detailed analysis of the most recent British Medical Association guidance from 2019. We argue that the guidance paints a confused and conflicting portrait of the law and ethics of the procedure in the UK context, reflecting deeper, unresolved moral and legal tensions surrounding child genital c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(56 citation statements)
references
References 135 publications
0
56
0
Order By: Relevance
“…Lempert et al [ 19 ] support particular statements in the BMA’s guidance[ 1 ] disfavoring NTMC. They refer to negative NTMC policies by Dutch (Kindermishandeling en huselijk geweld [KNMG]: Royal Dutch Medical Association), Danish and Finish medical bodies.…”
Section: Anti-ntmc Sentiments By Other Medical Bodiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Lempert et al [ 19 ] support particular statements in the BMA’s guidance[ 1 ] disfavoring NTMC. They refer to negative NTMC policies by Dutch (Kindermishandeling en huselijk geweld [KNMG]: Royal Dutch Medical Association), Danish and Finish medical bodies.…”
Section: Anti-ntmc Sentiments By Other Medical Bodiesmentioning
confidence: 99%
“…Various local bodies fighting the epidemic have also endorsed the procedure[ 21 - 26 ]. But presumably Lempert et al [ 19 ] had in mind socio-economically advantaged countries such as the UK and North America that have a relatively low HIV prevalence. The negative Canadian Paediatric Society policy nevertheless concluded that in Canada “there may be a benefit [from NTMC] for some boys in high-risk populations and circumstances ” [ 27 ].…”
Section: Anti-ntmc Sentiments By Other Medical Bodiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, even if one accepts the general evaluative framework depicted in Fig. 1, which is based on commonly accepted norms or standards within Western medical, pediatric, and sexual ethics [33][34][35], the question of where exactly to locate any given genital intervention vis-à-vis the axes of consent and medical necessity may in some cases remain controversial.…”
mentioning
confidence: 99%